Landfill leachate management in Istanbul: applications and alternatives - ÇALLI, BARIŞ; MERTOĞLU, BÜLENT (PERGAMON-ELSEVIER SCIENCE LTD, 2005)
Treatment alternatives for Istanbul, Komurcuoda Landfill (KL) leachate that is currently transported to the nearest central wastewater treatment plant were comprehensively investigated with laboratory scale experiments. As flow rate of leachate increases parallel to increment in landfilled solid waste, an individual treatment will be needed to reduce the transportation cost and pollution load on central treatment. However, if the leachate is separately treated and discharged to a brook, in that case more stringent discharge standards will be valid and therefore advanced processes in addition to conventional ones should be included. In laboratory scale experiments, the young landfill leachate having BOD5/COD ratio above 0.6 was successfully treated with efficiencies above 90% in upflow anaerobic reactors if pH is kept below free ammonia inhibition level. Subsequently, nitrification of anaerobically treated leachate was performed with rates of about 8.5 mg NH4+-Ng(-1) VSS h(-1) and efficiencies above 99% were provided with automated pH regulation by using sodium bicarbonate. Furthermore, denitrification rates as high as 8.1 mg NOx-Ng(-1) VSS h(-1) was obtained when carbon source was externally supplied. In addition to nitrification and denitrification, air stripping and struvite precipitation were also applied to remove ammonia in leachate and in average 94% and 98% efficiencies were achieved, respectively. Finally, in average 85% of biologically inert COD was successfully removed by using either ozone or Fenton's oxidation. © 2004 Elsevier Ltd. All rights reserved.
Keywords: Fenton's oxidation; denitrification; nitrification; ozonation; stripping; struvite precipitation; ANAEROBIC-AEROBIC TREATMENT; SEQUENCING BATCH; NITROGEN REMOVAL; AMMONIA REMOVAL; NITRIFICATION; REACTORS; PRETREATMENT; OXIDATION; DENITRIFICATION; SLUDGE